Utilization of ferrofluids in coal preparation - Turèániová ¼udmila; Lovás Michal; Mockovèiaková Annamária; Hredzák Slavomír; Jakabský tefan (Acta Montanistica Slovaca, 1998)
The contribution deals with the possibilities of ferrofluid application as a separation medium and a selective wetting agent with the aim of desulphurization and ash content decreasing of brown coal from Slovak deposits. The influence of magnetic field induction on sulphur and ash content in the products of magneto-hydrostatic separation was observed. The adsorption of ferrofluids on the surface of coal was observed. The ferrofluids cause above all the change of magnetic properties and they increase the separability of materials under magnetic field.